1997
DOI: 10.1002/(sici)1097-0029(19970801)38:3<329::aid-jemt13>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Local immune response in the skin of the external auditory meatus: An immunohistochemical study

Abstract: Cerumen plays an important role in the protection of the external auditory meatus against several kinds of damage. Its hydrophobic properties, due to the high concentration of lipids, shelter the canal from physical damages, while other components probably protect against certain microbial strains. Nevertheless there has been considerable dispute in the literature with regard to the antibacterial activity of cerumen. Because of the importance of the role of immunoglobulins (Ig) in local defense mechanisms, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Little work has been done to elucidate secretory proteins with immunohistochemical methods. Regarding the detection of isolated IgA-positive plasma cells near the ceruminous cells, our results are in accordance with those of Sirigu et al (1997). On the other hand, Ito et al (1993) found no staining of the secretory component of IgA in the human ceruminous gland, while we could clearly show a positive staining of the ceruminous cells for the secretory component; the coexistence of IgA and secretory component is likely and even compelling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Little work has been done to elucidate secretory proteins with immunohistochemical methods. Regarding the detection of isolated IgA-positive plasma cells near the ceruminous cells, our results are in accordance with those of Sirigu et al (1997). On the other hand, Ito et al (1993) found no staining of the secretory component of IgA in the human ceruminous gland, while we could clearly show a positive staining of the ceruminous cells for the secretory component; the coexistence of IgA and secretory component is likely and even compelling.…”
Section: Discussionsupporting
confidence: 89%
“…There are few histochemical studies dealing with components of the human ceruminous glands. Sirigu et al (1997) found in an immunohistochemical study isolated IgA, IgM, and IgG immunoreactive cells in the dermis surrounding human sebaceous and ceruminous glands. Human ceruminous glands contain acid phosphatase, nonspecific esterase, glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, and seem to secrete peroxidase (Sirigu et al, 1983).…”
mentioning
confidence: 96%
“…The secretion mixture of both gland types has been found to contain lipids, amino acids, glycoproteins and other components (see Chai & Chai 1980;Sirigu et al 1983;Roeser & Ballachanda 1997). The substances elaborated seem to protect the external auditory canal against various kinds of damage (Kataura & Kataura 1967;Chai & Chai 1980;Sirigu et al 1997;Welsch & Riedelsheimer 1997). Furthermore, dry-type human cerumen dissolved in buffer solution shows bactericidal activity against certain strains of common bacteria (Chai & Chai 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of these antimicrobial substances from skin glands may be required for an effective cutaneous innate immune response [6]. In the skin dermis, there is a type of gland that is composed of sebaceous glands and sweat glands.…”
Section: Discussionmentioning
confidence: 99%
“…The host defense of the skin in the EAC may depend on the physical barrier with the lateral migration and the slightly acidic pH (near 5.0) of the skin. In addition to the physicochemical barriers, the glands of EAC skin release various lipids and proteins [4] that are involved in protection against microbes [5,6]. The secretion that covers the canal skin is a mixture of ceruminous and sebaceous gland substances, of which ceruminous glands are the major source of cerumen.…”
Section: Introductionmentioning
confidence: 99%